Hemolysis due to Alpha-Hemolytic Enterococcus Urinary Infection: A Rare Cause of Early and Severe Unconjugated Hyperbilirubinemia in a Neonate - Karabulut, Birol; Gafil, Esin Alpagut (Journal of Pediatric Intensive Care, 2020)
The reason for reporting this case is to remind that some microorganisms may cause hemolysis leading to early and severe hyperbilirubinemia by secreting hemolysin in cases; where bilirubin levels cannot be successfully decreased despite effective phototherapy, intravenous immunoglobulin, and even exchange transfusion, or in cases of increased rebound bilirubin (although urinary tract infection is associated with increased conjugated bilirubin fraction and prolonged jaundice). The most common causes of hemolysis are ABO/Rh incompatibility and enzyme deficiencies such as glucose-6-phosphate dehydrogenase (G6PDH), pyruvate kinase (PK), and galactose-1-phosphate uridyltransferase (GALT). Our patient was a male infant, weighing 3,160 g, at 38 + 4 gestational week; he was referred to our unit with total bilirubin level of 14.7 mg/dL recorded at the postnatal 20th hour and was initiated treatment with intensive phototherapy and prepared for exchange transfusion. The G6PD, PK, and GALT enzyme levels studied at the postnatal 96th hour and reducing substances in urine were detected to be normal/negative, whereas complete urinalysis revealed pyuria (7 leukocytes per each high power field). α-hemolysis-producing 105 colony-forming unit/mL Enterobacter cloacae grew on blood agar in the urine culture. As reported in our case, hemolysin-secreting α and β-hemolytic bacteria can lead to severe and early hemolysis and unconjugated hyperbilirubinemia, as in blood type incompatibility and enzyme deficiencies.
Keywords: hemolysis; unconjugated hyperbilirubinemia; neonate